Antioxidant Properties of Spices, Herbs and Other Sources - Charles, Denys J. (Springer New York : Imprint: Springer, 2013)
Most natural antioxidants are common food components and have been widely used in diets for thousands of years. Recently, much focus has been given to the involvement of active oxygen and free radicals in aging and in disease processes like heart disease, inflammation, arthritis, immune system impairment and cancer. The importance of these antioxidants present in foods has been well appreciated for both preserving the foods themselves and supplying essential antioxidants in vivo. It is now widely accepted that the plant-based diets with high intake of herbs, spices, fruits, vegetables and other nutrient-rich plant foods help in reducing the risk of oxidative stress-related diseases. Plants have high concentrations of antioxidants, such as polyphenols, carotenoids, tocopherols, tocotrienols, glutathione, ascorbic acid and enzymes with antioxidant activity, which help to protect them from hazardous oxidative damage. Humans have a long history of using herbs and spices in their daily life as medicine and food preservatives. Herbs and spices are great sources of antioxidants and recent research has focused on their antioxidant properties. However, there are other natural products such as cereals, nuts, oilseeds, legumes, vegetables, animal products and microbial products which can serve as rich sources of natural antioxidants. The beneficial influence of many foodstuffs and beverages, including herbs, spices, teas, fruits, vegetables, coffee and cacao on human health has been recently recognized to originate from their antioxidant activity. The first part of the book describes the different methods used to measure antioxidant content as well as the various types of antioxidants present in different sources. In addition, the antioxidant properties of different sources are presented in great detail. The second part of the book consists of fifty-two chapters, where each chapter discusses one herb or spice, covering in detail botany, history, regions of production, flavor and aroma, parts used, preparation and consumption in different recipes, and functional and antioxidant properties. Dr. Denys J. Charles is Director of Research at Frontier Natural Products Co-op, Iowa, USA.